2016
DOI: 10.5796/electrochemistry.84.315
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrocatalytic Oxygen Reaction and Chloride Inhibition Resistance of Laccase Immobilized on Single-walled Carbon Nanotube and Carbon Paper Electrodes

Abstract: The rate of heterogeneous direct electron transfer of laccase immobilized on single-walled carbon nanotube (SWCNT) and carbon paper electrodes was evaluated by cyclic voltammetry and background-current-corrected steady-state linear voltammetry. These rates indicated that the molecular orientation of laccase immobilized on the SWCNT electrode was more favorable for direct electron transfer, than that of laccase immobilized on the carbon paper electrode. The inhibition of the bioelectrocatalytic O 2 reduction cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 32 publications
(61 reference statements)
6
20
0
Order By: Relevance
“…Figure 5D shows cyclic voltammetry of the BOD reactivation at pH 7 without inhibitor, where it is possible to displace F − , recovering 95% of the activity. These results are in agreement with those published by other authors, which suggest that F − ions inhibit DET and MET [55][56][57]. Another halide that inhibits the BOD is Cl − .…”
Section: Inhibitory Effectsupporting
confidence: 93%
See 2 more Smart Citations
“…Figure 5D shows cyclic voltammetry of the BOD reactivation at pH 7 without inhibitor, where it is possible to displace F − , recovering 95% of the activity. These results are in agreement with those published by other authors, which suggest that F − ions inhibit DET and MET [55][56][57]. Another halide that inhibits the BOD is Cl − .…”
Section: Inhibitory Effectsupporting
confidence: 93%
“…After using a fresh buffer solution no hysteresis were observed. Cl − showed a competitive inhibition [56,57]. Nevertheless, the inhibition process occurred only during DET and at very high concentrations of NaCl (>0.1 M).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Naki et al reported a kinetic study of Polyporus versicolor Lc showing that Cl − was a competitive inhibitor with respect to the electron donor substrate (ferrocyanide), thus suggesting that the Cl − was binding to or near the T1 site [10]. Furthermore, bioelectrocatalytic studies of Lcs have shown that direct electron transfer (DET) from the electrode to the enzyme is much less affected by Cl − than the mediated electron transfer (MET) using different substrates, whereas F − blocks both electron transfer modes [17][18][19][20]. This result was explained by considering that Cl − binds near the substrate binding site, precluding T1 reduction by the substrate but not electron transfer from the electrode.…”
mentioning
confidence: 99%
“…SC molecules act as an insulating barrier and inhibit fast electron transfer when the SC molecules form a multilayer on the HOPG interface. The electron transfer rate constant (k˚') for Lac at the SC-modified HOPG was evaluated by previously reported methods [25][26][27]. Figure 7a shows the catalytic current steady-state voltammograms and their fittings with simulated plots (Supplementary Material).…”
Section: = (−2 )mentioning
confidence: 99%